Pemberdayaan Desa dalam Pemanfaatan TIK di Desa Cihideunggirang Kabupaten Kuningan - Erik Kurniadi; Dadan Nugraha; Endra Suseno (Jurnal Pengabdian Masyarakat Madani, 2023)
The village development is no longer the authority of the central government authority but the authority of the regional government is more dominant in organizing, planning and making development policies in accordance with Law no. 32 of 2004. The policy of local government authorities is to facilitate the achievement of the level of community welfare. Structural changes in government that began in 1999 in the government structure that is close and directly in contact with the community, namely the village government. The implementation of village governance is still in the nature of public and administrative services. With the stipulation of Permendagri No. 84 of 2015 concerning the organizational structure and working procedures of the village government. Therefore, village involvement in development consists of village government stakeholders, community organizations and community leaders. The Cihideunggirrang village government in its performance must be supported by superior and professional human resources. The human resources of the Cihideunggirang village government must always be improved either through seminars, counseling, or training. To optimize the improvement of human resources in the Cihideunggirang village government, as village officials in all their activities must be supported by facilities and capabilities in the field of technology. This is very important because by involving technology, all the work carried out by the Cihideunggirang village apparatus can be assisted effectively.